The Role of Perpetuating Factors in the Development of Substance Use Disorder Among Adolescents - Khan Doutani , Mujeebullah; Doutani, Jamila; Naseeb Ullah,; Qadir, Abdul; Naila,; Wasay, Abdul; Kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Adolescence is marked by physical, emotional, and environmental changes, making individuals vulnerable to substance use. Personality traits, family dynamics, and emotional instability are significant perpetuating factors contributing to the rising rates of adolescent substance use globally and in Pakistan. Objective: The present study aimed conducted to explore the underlying causes or perpetuating factors for substance use among adolescents in Pakistan. Method: The qualitative study was conducted both from male and female participants of substance use disorder. The sample of the study consisted N=06 participants with the use of Substance use (M=03, F=03) with the age range of 18 to 24. The semi structure interview was conducted to explore the Perpetuating factors which lead towards the use of addiction. The interviews were audio-recorded and transcribed by independent researchers. Results: Thematic analysis was used as an approach to analyze the data collected through semi structured interviews. The themes were merged under the main three heading these were: ecological factors, constitutional vulnerability factors and psychological or individual factors which were the main triggering factors tend towards the usage of substance use among adolescents. Conclusion: The study reveals key themes such as personality traits, mood shifts, low self-esteem, and ecological influences as significant factors. Participants emphasized the impact of family issues and interpersonal conflicts, highlighting the importance of addressing these areas in understanding and managing substance use disorder among adolescents.